Experimental investigation and micromechanical modeling of mechanical and durability properties of concrete based on shells from sediments. (October 2022) - Beddaa, Hamza; Lavergne, Francis; Ben Fraj, Amor; Barthélémy, Jean-François; Torrenti, Jean-Michel
Abstract: The effect of substituting coarse aggregates with Corbicula shells on the mechanical and durability properties of concrete is evaluated by combining experimental investigations and micromechanical modeling. While substituting 20% of the aggregate volume with Corbicula shells does not affect slump, porosity, carbonation or chloride diffusion, a total replacement decreases slump, increases porosity and carbonation depth. Regarding mechanical properties, Young's modulus and compressive strength decrease linearly with the incorporation rate of Corbicula shells. The shells are then modeled as non-spherical inclusions surrounded by an interfacial transition zone and embedded in a cementitious matrix, so that micromechanical models provide estimates of mechanical and diffusion properties. Combining the model and experimental results reveals that the low stiffness and drop in compressive strength of the concrete are explained by a weak adhesion between the shells and the cementitious matrix. Highlights: The shells incorporation decreases the mechanical properties. The incorporation of shells up to 20% has no or minor effect on the slump and durability properties. The micromechanical model explains the drop in mechanical properties by a weak mortar–shell bond. The diffusion depends both on the shell–mortar bond and the shells orientation.